Comparative evaluation of the therapeutic effect of combined schemes for therapy and rehabilitation in acute respiratory infections with the inclusion of immunocorrective and sedative agents in children from 6 months to 6 years on the background of stress disorders in the conditions of war in Ukraine - I.O. Mityuryayeva-Kornijko; Ie.A. Burlaka; T.D. Klets; O.A. Panchenko; A.V. Kabantseva; D.S. Bardas (Zaslavsky O.Yu., 2024)
Background. Acute respiratory infections (ARIs) are one of the most common groups of diseases in the practice of pediatricians. Stressful factors affect the immune system, reducing its effectiveness and leading to direct impact on the nervous system and the occurrence of its disorders: sleep changes, the development of a post-traumatic stress disorder, a decrease in the quality of life, especially during the last years in wartime conditions in Ukraine. The latter requires improving the implementation of combined therapeutic approaches to increase a short- and long-term effect on the health of the youngest children. Aim of the study: to increase the effectiveness of treatment and rehabilitation of children from the youngest age group (6 months to 6 years) with ARIs against the background of stress disorders of the war in Ukraine by using comprehensive schemes with the inclusion of immunocorrective (the drug with immunocorrective properties contained a complex of ultra-low-dose dilutions of gamma interferon antibodies, histamine antibodies, CD4 antibodies) and sedative (the drug with sedative properties contained antibodies to the brain-specific protein S100) agents. Material and methods. The study involved 119 children aged 6 months to 6 years who had ≥ 5 episodes of ARIs (55 %) during the previous year and permanently lived in almost the entire territory of Ukraine (Kyiv, Kharkiv, Lviv, Dnipro, Zaporizhzhia, Odesa, Kropyvnytskyi, Vinnytsia, Kryvyi Rih, Zhytomyr, Cherkasy, Poltava, Sumy, Berdychiv, Romny, Bila Tserkva). The study was carried out as part of the program for outpatient observation of children with various manifestations of ARIs against the background of stress damage to the nervous system who took drugs with immunocorrective properties (scheme (1)) alone and in combination with a sedative agent (scheme (1+2)). The drug with immunocorrective properties contained a complex of ultra-low-dose dilutions of gamma interferon antibodies, histamine antibodies, CD4 antibodies, and the drug with sedative properties - antibodies to the brain-specific protein S100. The observation period was October-December 2023. Statistical processing of the results was carried out using GraphPad Prism 9.0 Software for Windows (USA, San Diego, CA). Results. The combined therapeutic approach of the scheme (1+2) showed a significantly better effect on fever, duration of low fever, sore throat, runny nose, bronchitis symptoms, manifestations of respiratory infection, assessed by the Wisconsin Questionnaire, as well as stress, sleep disorders, and changes in the quality of life on the 5th day of treatment and after 1 month of observation. The comparative evaluation of scheme (1) and scheme (1+2) showed a significant difference in favor of the effectiveness of the latter, which is ensured by its additional sedative and anti-anxiety action, resulting in a direct positive effect on stress-induced disturbances of the nervous system and an indirect - on the immune response, which in general increases the effectiveness of solving the problem of ARI therapy in children aged 6 months to 6 years, who for 2.5 years were constantly in psycho-traumatizing and socially oppressed conditions of the war in Ukraine. The analysis of satisfaction with the treatment effect according to the international IMOS scale during the observation period showed positive results and a high level of evaluation by both parents and doctors. Conclusions. The use of a combination of remedies with immunocorrective and sedative effects showed their high mutual enhancing effectiveness in the treatment and rehabilitation of children aged 6 months to 6 years, suffering from ARIs, and in the correction of stress disorders caused by the war in Ukraine.